Establishment of a tetracycline-off and heat shock-on gene expression system in tobacco - You ZHOU; Jin-hua LI; Yu PAN; Yu ZHENG; Yang-lu PAN; Yu-mei DING; Cheng-gang SU; Xing-guo ZHANG (Journal of Integrative Agriculture, 2017)
The tetracycline (Tet)-off gene expression regulation system based on the TetR-VP16/Top10 construct has not been widely utilized in plants, for its highly expressed TetR-VP16 activator is toxic to some plants and repeatedly replenishing tetracycline to turn off the constitutively active system is a tedious process. To solve these problems, a Tet-off and heat shock (HS)-on gene expression regulation system was constructed in this study. This system is composed of a chimeric transactivator gene TetR-HSF that is derived from a Tet repressor (TetR) and a HS transcription factor (HSF) controlled by a HS promoter HSP70m, and a Tet operator containing hybrid promoter, Om35S, that drives expression of the β-glucuronidase (GUS) gene. The resultant system yields a GUS expression pattern similar to that of the HSP70m promoter under inducing temperatures and at 35 and 40°C drives GUS expression to a similar level as the Cauliflower mosaic virus (CaMV) 35S promoter. Further examination revealed that the TetR-HSF and GUS genes were induced by HS, reaching peak expression after 1 and 6 h treatment, respectively, and the HS induction of the expression system could be inhibited by Tet. This system will provide a useful tool for transgenic studies of plants in the laboratory and in the field, including transgene function analysis, agronomic trait improvement, biopharmaceutical protein production and others.